The Effectiveness of Pair Work Activities on Students’ Speaking Anxiety and Speaking Ability - Rahmah Rianti; Abdul Syahid; Zaitun Qamariah (Universitas Majalengka, 2022)
Students' anxiety about speaking English is significant to solve because it can affect their speaking ability. This study aims to measure the effectiveness of pair work activities on students’ speaking anxiety and speaking ability. The researchers conducted quasi-experimental research in Palangka Raya in the academic year of 2021/2022. In collecting the data, a questionnaire and a speaking test were used. The population in this study were eighth graders students in one of the public junior high school. The researcher used two classes as the sample, the experimental and control class, which comprised 60 students. The data were analyzed using the descriptive statistics and Multivariate Analysis of Variance test via SPSS.23. The result showed pair work activities effectively decreased the students’ speaking anxiety and increased the students' speaking ability. It evidenced by the average score in the post-test of students' speaking anxiety in the experimental class was 52.77, while the control class was 60.00. In addition, the average score in the post-test of the students’ speaking ability in the experimental class was 76.63, while the control class was 64.43. It showed that there is a significant difference between the two classes. Therefore, this study indicates that pair work activities effectively lower students' speaking anxiety and increase their speaking ability at eighth graders students in one of the public junior high school in Palangka Raya.